Documented bites by a yellow sac spider (Cheiracanthium punctorium) in Italy: a case report - Papini,R (2012)
In Italy reports of human envenomations by yellow sac spiders have been sporadic. Since increasing clinical information would improve understanding of the danger of yellow sac spiders to humans, we report the case of a 7-year-old child and her father bitten by a documented Cheiracanthium punctorium. They developed acute persistent pain with local skin signs and numbness, and required emergency treatment. The father recovered completely within 1 to 2 hours and the child within 3 to 4 days after treatment, probably as a result of spontaneous evolution. Clinicians should be aware of the risks and immediate management of spider bites.